"Walking on both sides of the fence": A qualitative exploration of the challenges and opportunities facing emergent clinician‐scientists in child health. Issue 1 (14th June 2022) - Pritchard, Lesley; Bright, Katherine S.; Walsh, Catharine M.; Samuel, Susan; Li, Queenie K. W.; Wollny, Krista; Twilt, Marinka; Tomfohr‐Madsen, Lianne; Pires, Linda; Dimitropoulos, Gina
Abstract: Rationale, Aims, and Objectives: While paediatric clinician‐scientists are ideally positioned to generate clinically relevant research and translate research evidence into practice, they face challenges in this dual role. The authors sought to explore the unique contributions, opportunities, and challenges of paediatric clinician‐scientists, including issues related to training and ongoing support needs to ensure their success. Method: The authors used a qualitative descriptive approach with thematic analysis to explore the experiences of clinician‐scientist stakeholders in child health ( n = 39). Semi‐structured interviews (60 min) were conducted virtually and recorded. Thematic analysis was conducted according to the phases outlined by Braun and Clarke (2006). Results: The analysis resulted in the creation of three themes: (1) "Walking on both sides of the fence": unique positioning of clinician‐scientists for advancing clinical practice and research; (2) the clinician‐scientist: a specialized role with significant challenges; and (3) beyond the basics of clinical and research training programmes: essential skill sets and knowledge for future clinician‐scientists. Conclusions: While clinician‐scientists can make unique contributions to the advancement of evidence‐based practice, they face significant barriers straddling their dual roles including divergent institutional cultures in healthcare and academia and a lack of infrastructure to effectively support clinician‐scientist positions. Training programmes can play an important role in mentoring and supporting early‐career clinician‐scientists.